Large Drill Holes Are Still Present in the Long Term After Arthroscopic Bankart Repair With Absorbable Tacks: An 18-Year Randomized Prospective Study. Issue 8 (July 2020) - Constantinou, Christina Chrysanthou; Sernert, Ninni; Rostgård-Christensen, Lars; Kartus, Jüri
Background: Studies have demonstrated the development of an osseous reaction at the drill sites of anchors after arthroscopic shoulder surgery. Purpose: To investigate the drill-hole size at 18 years after arthroscopic Bankart repair using either fast polygluconate acid (PGA) or slow polylevolactic acid (PLLA) absorbable tacks and to compare the functional outcomes and development of osteoarthritis. Study design: Randomized controlled trial; Level of evidence, 2. Methods: 40 patients with unidirectional anterior shoulder instability, treated with arthroscopic Bankart repair, were randomized into the PGA group (n = 20) or the PLLA group (n = 20). Plain radiographs of both shoulders, as well as computed tomography (CT) images of the operated shoulder, were used to evaluate the drill-hole size, volume, and degenerative changes. Functional outcomes were assessed by use of the Rowe score, Constant score, and Western Ontario Shoulder Instability (WOSI) index. Results: Of the 40 patients, 32 patients returned for the follow-up (15 PGA and 17 PLLA). No significant differences were found in the population characteristics between the study groups. The mean follow-up time was 18 years for both groups. No significant differences were seen in range of motion, strength in abduction, or Constant, Rowe, and WOSI scores between the groups. Recurrence rate was 33% in the PGA group and 6% in the PLLA group during the follow-up period ( P = .07). The drill-hole appearance on plain radiographs (invisible/hardly visible/visible/cystic) was 11/2/2/0 and 6/5/5/1 for the PGA and PLLA groups, respectively ( P = .036). The mean ± SD drill-hole volume as estimated on CT images was 89 ± 94 and 184 ± 158 mm 3 in the PGA and PLLA groups, respectively ( P = .051). Degenerative changes (normal/minor/moderate/severe) on plain radiographs were 7/4/4/0 and 3/8/5/1 for the PGA and PLLA groups, respectively ( P = .21), and on CT images were 5/7/3/0 and 2/6/6/3 for the PGA and PLLA groups, respectively ( P = .030). Conclusion: This long-term follow-up study demonstrated that the PLLA group had significantly more visible drill holes than the PGA group on plain radiographs. However, this difference was not evident on CT imaging, with both groups having several visible cystic drill holes and a substantial drill-hole volume defect. No significant differences were found between the study groups in terms of clinical outcomes.